Development prototype of Faculty of Information Technology & Quantitative Sciences (FTMSK) online bidding education resources based on agile technique / Mohd Kahar Hassan - Hassan, Mohd Kahar (2008)
This research is about developing prototype of FTMSK Online Education Resources based on agile technique. Since, FTMSK community website does not have bidding application to sell the education resources. This system hopefully will help student of Faculty of Information Technology and Quantitative Sciences (FTMSK) to sell their education resources which is do not use anymore by using bidding application. So that, possibility to get satisfy price will be high if the student advertise their item through auction very interesting. Besides, it also possible that student will find the item which find up till now. For research element, this system is design based on agile method technique that is refactoring during design class phase. This technique a little bit can make small changes to your source code to improve its design, making it easier to work with.